South Africa's post-apartheid microcredit-driven calamity: Comparing 'developmental' to 'anti-developmental' local financial models - Milford Bateman (Austrian Foundation for Development Research (ÖFSE), 2014)
Microcredit was once universally lauded in international development community circles as a 'magic bullet'. Using the example of South Africa, this paper shows that microcredit has actually been an 'anti-developmental' local financial model, and one of the most calamitous financial sector interventions in South Africa's short post-apartheid history. This disastrous performance is compared to a benchmark local financial model that I call the 'developmental' local financial model, a financial model that was quite decisive to much recent European and Asian local economic development success. Overall, microcredit can be viewed as South Africa's own sub-prime-style disaster which, like the original US version, has mainly served to benefit a tiny financial elite working within and around the microcredit sector, whilst simultaneously destroying many of the most important pillars of the economy and society. It clearly behoves policymakers in South Africa, as well as policymakers in other African countries and elsewhere in the international development community, to learn from South Africa's negative experience with 'anti-developmental' microcredit to date and promote alternative 'developmental' local financial models.
Keywords: G2; H7; O2; O4; 330; Microcredit; South Africa; impact; poverty; informal; SME; institutions